2012
DOI: 10.1371/journal.pone.0044349
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in Hospitalised Children in Germany Are Decreasing: Results of a Nine Year Cohort-Based Comparison

Abstract: BackgroundIn recent years, efforts have been made to improve paediatric drug therapy. The aim of this research was to investigate any changes regarding the frequency and nature of adverse drug reactions (ADRs) in hospitalized children in one paediatric general medical ward over a 9-year period.MethodologyTwo prospective observational cohort studies were conducted at a large University hospital in Germany in 1999 and 2008, respectively. Children aged 0–18 years admitted to the study ward during the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…Though metamizole is a very effective analgesic and antipyretic and can be used in both adults and children, it is not available in some countries, e.g. the UK, because of its association with rare but life-threatening agranulocytosis and aplastic anaemia [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Germany, the respective figure was 1% [ 4 ]. In contrast, the ADR incidence in hospitalized children is estimated to be higher ranging from 9.53% [ 5 ] to 13.1% [ 6 ]. In comparison the incidence of hospitalisation of adult outpatients in Germany is 3.2% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%